The Behavioral Regulation in Exercise Questionnaire (BREQ-4): Psychometric evidence of introjected approach regulation in Portuguese health club exercisers - Teixeira, D.S. (2022)
The assessment of motivation has been a key aspect to the understanding of exercise participation, and research grounded in self-determination theory has presented valid and reliable instruments for that purpose. Given the need to continually refine this latent construct, the present study aimed to translate, adapt, and psychometrically validate a subscale targeting the approach facet of introjection, and to test the pattern of associations between motives for practice, basic psychological needs satisfaction/frustration, and behavioral regulations encompassing the validated introjection subscale, in a sample of health club exercisers. For that purpose, two studies were developed with a total of 1216 health club exercisers. In Study I (n = 806), Confirmatory Factor Analysis and Exploratory Structural Equation Modeling analysis to test the motivational continuum encompassing the introjected approach subscale were performed. In Study II (n = 410) associations and structural models between intrinsic and extrinsic goal contents, basic psychological needs satisfaction and frustration, and behavioral regulations with the new subscale were tested. The correlated seven-factor model with 21 items in Study I displayed good psychometric properties (CFA: χ2 = 481.977 (168), p < .001, CFI = 0.936, TLI = 0.915, SRMR = 0.037, RMSEA = 0.048; ESEM: χ2 = 178.672 (84), p < .001, CFI = 0.980, TLI = 0.949, SRMR = 0.014, RMSEA = 0.037). The introjected approach regulation added to the preexisting factorial structure did not affect the validity and reliability of the instrument. The results from Study II supported a theoretically expected pattern of associations, in which the introjected regulation of approach is positioned between introjected avoidance and identified regulation along the motivational continuum. Additionally, path estimates depicted criterion validity for the new subscale. All in all, this work presents preliminary evidence for an introjected approach regulation subscale that can be used in health club practices for a better understanding of the motivational quality of exercise practice.